2000
DOI: 10.1021/es991068l
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination ofl-Ascorbic Acid, Glutathione, and Their Oxidized Forms in Ozone-Exposed Vascular Plants by Capillary Zone Electrophoresis

Abstract: Simultaneous determination of ascorbic acid (AA), glutathione (GSH), and oxidized glutathione (GSSG) in vascular plants has been achieved by capillary zone electrophoresis. A background electrolyte containing a phosphate buffer of pH 7 and hexadimethrin bromide for dynamic control of electroosmotic flow was used. Separation was performed in less than 5 min. The signal was simultaneously monitored at 265 and 200 nm. Dehydroascorbic acid (DHA) was determined in another aliquot of the same plant extract upon redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 75 publications
4
15
0
Order By: Relevance
“…In this sense, our results confirm this tendency and are coincident with the results of several authors 5,8 . Likewise, the levels found in tomato root showed the same orders of magnitude as those reported by Rellan et al 8 in the root of Beta vulgaris, which they report as 92.1 and 46.1 nmol g -1 fr wt.…”
Section: Figuresupporting
confidence: 94%
See 4 more Smart Citations
“…In this sense, our results confirm this tendency and are coincident with the results of several authors 5,8 . Likewise, the levels found in tomato root showed the same orders of magnitude as those reported by Rellan et al 8 in the root of Beta vulgaris, which they report as 92.1 and 46.1 nmol g -1 fr wt.…”
Section: Figuresupporting
confidence: 94%
“…Similarly, linearity was good, with a correlation coefficient above 0.999 and a linear range up to 80 µM. Limit of detection values are comparable to those reported by Herrero et al 5 using CE with a diode array detector or those reported by Carru et al 12 using photometric detection. Values are also similar to those found through chromatographic techniques 8 , although not as low as those found through CE coupled to the use of more sensitive detectors such as laser-induced fluorescence 18 and mass spectrometry 19 .…”
Section: Figuresupporting
confidence: 85%
See 3 more Smart Citations